EFL TEACHERS SELF-REPORTED DIFFERENTIATED INSTRUCTIONAL PRACTICES AT KEFTEGNA 23 SECONDARY SCHOOL, ETHIOPIA - Melka, Yirmalem Girma; Beriso, Italo (Universitas PGRI Sumatera Barat, 2022)
The purpose of this study was to explore selected high school English teachers self-reported differentiated instructional practices that haven’t been addressed in the Ethiopian EFL context. To achieve this purpose, data was collected using questionnaire for EFL teachers and semi-structured interview students. The selected EFL teachers filled the questionnaire based on their willingness and the students were randomly selected from two sections and interviewed to cross-check the data obtained from their EFL teachers. The students were interviewed in Amharic and transcribed in to English and the data were analyzed descriptively. The results of the study indicated that EFL teachers’ perceive that their English classes are composed of students’ with different learning achievement levels consisting of very struggling, grade level and advanced students but instructional practices were not adequately responsive to the students different readiness levels. They rated their students as grade level/average achievers and take this group in to account while delivering English lessons. Besides, results showed that teaching to the middle level is most preferable. Findings further showed that EFL teachers had no experience of pre-assessing students’ different readiness levels or current status to make informed decisions, and hardly modify instruction and highly depend on textbook activities/tasks. Results from the interview further indicated that students experiencing or receiving the EFL teachers’ instructional practices were not perceived favorably. Thus, it is evident to conclude that the EFL teachers’ instructional practices were undifferentiated and it is suggested EFL teachers should get awareness trainings to integrate DI in to their teaching.